CaP cement is equivalent to iliac bone graft in filling of large metaphyseal defects: 2 year prospective randomised study on distal radius osteotomies. Issue 3 (March 2018) - Winge, Mona I.; Røkkum, Magne
Abstract: The purpose of this prospective randomised study was to compare the clinical and radiological outcomes of injectable CaP bone cement with corticocancellous bone graft used to fill voids after corrective opening wedge osteotomies in the distal radius. 17 women/3 men, median age 56 (51.3; 61.0), underwent an open-wedge osteotomy of a dorsal malunion in the distal radius randomised to filling the defect either with bone graft (10) or CaP bone cement (10). Dorsal titanium locking plates were used and the wrist was plastered for 8 weeks. Follow-ups for 24 months included X-rays, CT scans, VAS on wrist and iliac crest, grip strength, ROM, Quick-DASH and Gartland & Werley scores. No difference was found between the 2 groups as to clinical outcome or radiological results with no loss of reduction. One bone graft patient developed a pseudarthrosis and one CaP patient suffered a plate fracture 6 months post-operatively. CaP bone cement is a good alternative to bone graft as a void filler in open-wedge osteotomies of the distal radius. The procedure is shorter, easier with the post-operative advantage of no donor site pain. Level of Evidence Randomised controlled trial. Level I evidence.